Heavy Metals in Topsoil under Selected Vegetable Cultivation Areas in Cameron Highlands, Pahang, Malaysia - Abdul Rahim, Sahibin; Ali Rahman, Zulfahmi; Lihan, Tukimat; Omar, Ramlan; Hashim, Azman; E, Prihatino; K.M, Lai (Malaysian Journal of Science, 2006)
Heavy metal contents of soil under vegetable cultivation in the Cameron Highlands were determined. Five stations selected for this purpose were Kg. Raja (forest reserve), Kuala Terla (cabbage), Tringkap (cabbage) and two stations at Blue Valley (cabbage and an abandoned tea plantation). Soil samples were collected during the harvesting season for cabbage. Soil in the tea plantation and forest were used for comparison. The mean of all of the heavy metals examined, except arsenic, were high in soil cultivated with cabbage compared to the soil under natural forest and tea plantation. The increase in heavy metal content for the agricultural area was attributed to the common practice of fertilizing, liming and pest control. Heavy metal content in all stations was within the normal range in soils but As and Zn concentrations were already within the potential toxic threshold in soil. Soil parameters such as pH, organic matter, silt and phosphorus content in soil had an influence on the enrichment of Pb, Co, Ni, Zn and Cr in soil.